Board Attributes and Firm Performance During The Covid-19 Pandemic: Evidence From Sri Lanka - Tharsika, K.; Sayanthan, B.; Pratheepkanth, P. (4th Research Conference on Business Studies (RCBS) - 2022 (p. 12). Vavuniya: University of Vavuniya., 2022)
Over the last three years, coronavirus has been a hotly debated topic among academics and professionals. It has an impact not only on people's health but also on the economies of both developed and developing countries. However, there is a limited empirical support in both developed and developing countries, particularly in Sri Lanka, for answering the the relationship between board characteristics and firm performance prior torelationship isrelationship between board characteristics and firm performance before and after during the Coronavirus. As a result, this study aims to look into the impact of board characteristics on firm performance in 176 non financial listed firms in Sri Lanka before and after COVID-19. The findings indicate that board attributes, particularly board size, significantly impact firm performance before and during the pandemic. However, in both periods, board independence and board meetings are unrelated to ROA. As a result, the large number of people on board helps ensure the firm’s long-term viability in unavoidable circumstances. The implications of this result are to assist regulators, policymakers, and company managers in designing board attributes during an unavoidable situation
Keywords: Board attributes; COVID-19; Firm performance